2020
DOI: 10.1088/1755-1315/443/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extraction process of coffee pulp as a source of antioxidant

Abstract: Coffee pulp is a by-product of coffee cherry processing during the production of coffee beans, and is usually disposed of as waste or used as compost. The valorization of coffee pulp is very important since a large quantity of coffee pulp is produced during coffee processing. In this study, the coffee pulp was extracted using various solvents at different temperatures and times to maximize the total phenolic content and the antioxidant activity of the extract. The total phenolic content was analyzed using Foli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…While organic compounds, such as ethanol and methanol are considered the optimal solvents to extract phenolic compounds [56], the presented methodology can be posed as a quick, green strategy to enhance phenolic yield and antioxidant content using water as the main process solvent. In the case of coffee pulps, this study shows reduced yields to the approach used by Kusumocahyo et al [57], a solid-liquid extraction carried out at 60 °C and 60 min (2612 mg GAE/100 g coffee pulp). Nevertheless, the process involves a two-step extraction using n-hexane and a mixture of water and ethanol to optimize its extraction yield.…”
Section: And Ferric Reducing Antioxidant Power Quantitation (Frap) As...mentioning
confidence: 57%
“…While organic compounds, such as ethanol and methanol are considered the optimal solvents to extract phenolic compounds [56], the presented methodology can be posed as a quick, green strategy to enhance phenolic yield and antioxidant content using water as the main process solvent. In the case of coffee pulps, this study shows reduced yields to the approach used by Kusumocahyo et al [57], a solid-liquid extraction carried out at 60 °C and 60 min (2612 mg GAE/100 g coffee pulp). Nevertheless, the process involves a two-step extraction using n-hexane and a mixture of water and ethanol to optimize its extraction yield.…”
Section: And Ferric Reducing Antioxidant Power Quantitation (Frap) As...mentioning
confidence: 57%
“…The IC50 in this study was affected by decaffeination time (B), decaffeination temperature (C), the interaction between extraction time and decaffeination temperature (AC), the interaction between decaffeination time and decaffeination temperature (BC), decaffeination time (B 2 ) and decaffeination temperature (C 2 ) in a quadratic term. Figure 3(A [50] reported that the IC50 and total phenolic content have a reverse correlation: the high total phenolic content caused the lower IC50 in another. Muchtaridi et al [16] stated that decaffeination not only decreases the concentration of caffeine but also decreases the concentration of chlorogenic acid.…”
Section: Antioxidant Activity (Ic50)mentioning
confidence: 98%
“…It has been used to produce CP beverages due to its content of sugars, polyphenols (rutin, gallic acid, protocatechuic acid, and chlorogenic acid), and caffeine [63]; for the same reasons, it has also been used in the formulation of infusions [64]. The approach proposed by Kusumocahyo et al, in which bioactive compounds from CP are obtained using spray drying, could be an interesting area for research, since this technology could preserve the antioxidant properties of the extract and allow its use in multiple products [65]. Moreover, the extracts from CP have been included in one study as an anti-inflammatory compound in a food supplement [66].…”
Section: Foodmentioning
confidence: 99%